Walking the Tightrope: Avoiding a Lockdown While Containing the Virus - Balázs Égert; Yvan Guillemette; Murtin Fabrice; David Turner (CESifo Forum, 2021)
This paper finds that although containment policies can successfully reduce the spread of the virus, they can also have a substantial impact on reducing mobility and economic activity. It also shows that testing, combined with effective contact tracing, is crucial in reducing the spread of the virus, especially at relatively low levels of infection, and that mask-wearing and the protection of the elderly population in general and those in care homes in particular, might play an important role in combatting the virus while minimizing economic costs.
Keywords: 330